INFLUENCE OF GROSS REGIONAL DOMESTIC PRODUCT AND OPEN UNEMPLOYMENT RATE ON THE HUMAN DEVELOPMENT INDEKS IN LAMPUNG PROVINCE FOR THE YEARS 2017-2021 - Gana Perkasa Jafba; Reza Juanda (LPPM Universitas Malikussaleh, 2023)
This research aims to determine the influence of Gross Regional Domestic Product (GRDP) and Open Unemployment Rate (OUR) on the Human Development Index (HDI) in Lampung Province for the years 2017-2021. The data used is secondary data obtained from the Central Statistics Agency (BPS), which includes data from each of the 15 districts/cities in Lampung Province. The research method employed is quantitative. The data was analyzed using panel data regression method by combining the data of the 15 districts/cities in Lampung Province along with GRDP, OUR, and HDI data from 2017 to 2021. The t-test results indicate that Gross Regional Domestic Product has a positive and significant impact on the Human Development Index in Lampung Province for the years 2017-2021. The Open Unemployment Rate has a positive and significant impact on the Human Development Index in Lampung Province for the years 2017-2021. The f-test results show that both Gross Regional Domestic Product and Open Unemployment Rate have an impact on the Human Development Index in Lampung Province for the years 2017-2021. The panel data regression results indicate that the city of Mesuji has the highest constant at -57.34%. Additionally, the coefficient of determination (R2) in this study is 97%, meaning that the variables of Gross Regional Domestic Product and Open Unemployment Rate collectively explain 97% of the variation in the Human Development Index, while the remaining 3% is influenced by other variables.